PENGARUH ACCOUNT OFFICER DAN PROMOSI TERHADAP KEPUTUSAN MENGAMBIL PRODUK PEMBIAYAAN DI BMT UGT SIDOGIRI CAPEM PESANGGARAN KABUPATEN BANYUWANGI - Hasan Abdillah Agung Ramadlony; Muhamad Annas (Jurnal Ekonomi Syariah Darussalam, 2025)
The purpose of this study was to determine whether there is an influence between the role of the account officer on the decision to take financing products in BMT UGT Sidogiri, a subsidiary of Pesanggaran. To find out whether there is an effect of promotion on the decision to take financing products in BMT UGT Sidogiri Pesanggaran subsidiary branch. This research method is quantitative, where data colletion uses observations, interviews, documentatin, and questionnaires. The sample of the study was 30 respondents who were members of financing products. Sample were taken using simple random sampling technique. The independent variable in this study are the account officer (X1) and promotion (X2) while the dependent variable is the decision to take financing product (Y). Data analysis used is multiple linier regression. The conclusion of this study is that partially there is a significant influence of the account officer on the decision to take financing products. There is a promotion influence on the decision to take financing products. And simultaneous account officers and promotions influence the decision to take financing product in BMT UGT Sidogiri, a subsidiary of Pesanggaran.